Enhancing financial education in lower primary with concrete kits and digital teaching apps - Hock, Tan Tong; Mohd Ayub, Ahmad Fauzi; Hidayat, Riyan (Human Resources Management Academic Research Society (HRMARS), 2024)
Money is significant and should be understood and mastered by students since young age. However, students still face difficulties learning and getting the concept of money, especially in today's digital age. Therefore, this study aims to determine the effectiveness of using concrete money learning kits and digital teaching apps in enhancing the understanding of money concepts among second-grade students. The study respondents were 30 students who went through the lesson study using concrete and digital learning kits. The learning process of the concept of money included the introduction of money, operation in using money, exchange of money, and solving daily money problems. Data collection using test instruments was then analyzed using a marking scheme. Data analysis used to test the study hypotheses was paired with a T-test for the performance before and after the lesson study. The study's findings showed that the lesson study conducted successfully improved the achievement of second-year students in learning the concept of money. This study shows that concrete and digital learning kits can help students conceptual understand and promote meaningful mathematical learning. The implication to students is that they can improve their Mathematics achievement on money, especially in this era of e-money.